2015
DOI: 10.1021/acs.jproteome.5b00965
|View full text |Cite
|
Sign up to set email alerts
|

Deep Quantitative Proteomics Reveals Extensive Metabolic Reprogramming and Cancer-Like Changes of Ectopic Endometriotic Stromal Cells

Abstract: Endometriosis is a prevalent health condition in women of reproductive age characterized by ectopic growth of endometrial-like tissue in the extrauterine environment. Thorough understanding of the molecular mechanisms underlying the disease is still incomplete. We dissected eutopic and ectopic endometrial primary stromal cell proteomes to a depth of nearly 6900 proteins using quantitative mass spectrometry with a spike-in SILAC standard. Acquired data revealed metabolic reprogramming of ectopic stromal cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 60 publications
1
46
0
3
Order By: Relevance
“…In recent years, accumulating evidence has suggested that significant biological differences exist between the eutopic endometria of healthy women and the ectopic endometria of women with endometriosis [3, 23], but few studies have identified significant biochemical differences between the ectopic endometriotic lesions and the putative eutopic precursors [24]. Thus, in our study, we analyzed the differentially expressed peptides between the eutopic and ectopic endometria of OvE patients, a common subtype of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, accumulating evidence has suggested that significant biological differences exist between the eutopic endometria of healthy women and the ectopic endometria of women with endometriosis [3, 23], but few studies have identified significant biochemical differences between the ectopic endometriotic lesions and the putative eutopic precursors [24]. Thus, in our study, we analyzed the differentially expressed peptides between the eutopic and ectopic endometria of OvE patients, a common subtype of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Эндометриоз рассматривается как доброкаче-ственное заболевание, однако он имеет некоторые биологические особенности, характерные для рака, такие как клеточная инвазия, развитие новых крове-носных сосудов, неконтролируемый рост, резистен-ция к апоптозу, способность к метастазированию и хроническое воспаление [51,52]. Исследования по-казали, что эндометриоидные очаги при эндометри-озассоциированном раке яичников проходят много-ступенчатую трансформацию от типичного к ати-пичному эндометриозу, а затем к раку [51].…”
Section: повышение пролиферативной активности и супрессия апоптозаunclassified
“…Исследования по-казали, что эндометриоидные очаги при эндометри-озассоциированном раке яичников проходят много-ступенчатую трансформацию от типичного к ати-пичному эндометриозу, а затем к раку [51]. Относи-тельно частоты некоторые авторы оценивают риск в 1% для развития опухолей из эндометриальной тка-ни [51][52][53].…”
Section: повышение пролиферативной активности и супрессия апоптозаunclassified
See 1 more Smart Citation
“…In order to implant, endometrial fragments have to first penetrate either through intact barriers consisting of epithelial cells, basement membranes and collagen or directly through surgical scars and then spread 6 . In this regard, endometriosis shares many similarities with metastatic cancer 7 . Nevertheless, while cancer researchers have devoted considerable attention to dissecting the invasive processes involved in cancer metastases 8 , little is known about invasive processes in endometriosis.…”
Section: Introductionmentioning
confidence: 99%